Estimation methods of information intensity of the tracklaying vehicle driver's work - M. Y. Manzin (Вестник СибАДИ, 2017)
The article considers the estimation technique of information intensity of the tracklaying vehicle driver's work. It is based on the estimation technique of the information contentof both anisolated irregularity and a track section as a whole. This technique allows predicting the value of the average speed of the tracklaying vehicle provided with driver'sabilities to process and implement the incoming information on the ambient traffic conditions. The article can be useful forre-searchers, engineers and techniciansregardingvehicle handling trial, who deal with practical aspects of tests and evaluation of ergonomic vehicle properties and, in particular, ergonomics of the driver's compartment.